1989
DOI: 10.1126/science.2548279
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Folding in Retroviral Proteases: Crystal Structure of Synthetic HIV-1 Protease

Abstract: The rational design of drugs that can inhibit the action of viral proteases depends on obtaining accurate structures of these enzymes. The crystal structure of chemically synthesized HIV-1 protease has been determined at 2.8 angstrom resolution (R factor of 0.184) with the use of a model based on the Rous sarcoma virus protease structure. In this enzymatically active protein, the cysteines were replaced by alpha-amino-n-butyric acid, a nongenetically coded amino acid. This structure, in which all 99 amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
744
0
7

Year Published

1992
1992
1999
1999

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 1,150 publications
(765 citation statements)
references
References 28 publications
14
744
0
7
Order By: Relevance
“…5A; Kinemage 2). Although the apoenzyme of HIV-1 PR is strictly symmetric under conditions of the investigation of its crystals reported previously (Lapatto et al, 1989;Navia et al, 1989;Wlodawer et al, 1989), most of the inhibitors studied so far are asymmetric, and thus the two molecules in the protein dimer of the resulting complex are nonequivalent. It was reported that this asymmetry is present even in the complexes of protease with quasisymmetric inhibitors Bone et al, 1991).…”
Section: I F O Imentioning
confidence: 92%
“…5A; Kinemage 2). Although the apoenzyme of HIV-1 PR is strictly symmetric under conditions of the investigation of its crystals reported previously (Lapatto et al, 1989;Navia et al, 1989;Wlodawer et al, 1989), most of the inhibitors studied so far are asymmetric, and thus the two molecules in the protein dimer of the resulting complex are nonequivalent. It was reported that this asymmetry is present even in the complexes of protease with quasisymmetric inhibitors Bone et al, 1991).…”
Section: I F O Imentioning
confidence: 92%
“…The crystal structures of the human immunodeficiency virus 1 (HIVl) (Navia et al, 1989;Wlodawer et al, 1989) and Rous sarcoma virus (RSV) PRs confirmed the homodimeric nature of these viral enzymes and also defined the regions of interaction between the monomers. The extensive hydrophobic interface present in these PR dimers is dominated by a n antiparallel P-sheet formed by the interdigitation of the N-terminal (residues 1-4 in HIVl and 1-5 in RSV) and the C-terminal (residues 96-99 in HIVl and 119-124 in RSV) 0-strands of each monomer ( Fig.…”
Section: Introductionmentioning
confidence: 88%
“…The functional structure of HN-1 protease is a homodimer in which each monomer contributes one of the two catalytic aspartic acids in the active site (Lapatto et al, 1989;Navia et al, 1989;Wlodawer et al, 1989). The catalytic apparatus of HIV-1 protease is nearly identical to that of the pepsin-like proteases of the eu- karyotes, except for one major structural difference.…”
mentioning
confidence: 99%